1994
DOI: 10.1002/j.1460-2075.1994.tb06432.x
|View full text |Cite
|
Sign up to set email alerts
|

A conserved secondary structural motif in 23S rRNA defines the site of interaction of amicetin, a universal inhibitor of peptide bond formation.

Abstract: The binding site and probable site of action have been determined for the universal antibiotic amicetin which inhibits peptide bond formation. Evidence from in vivo mutants, site‐directed mutations and chemical footprinting all implicate a highly conserved motif in the secondary structure of the 23S‐like rRNA close to the central circle of domain V. We infer that this motif lies at, or close to, the catalytic site in the peptidyl transfer centre. The binding site of amicetin is the first of a group of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 21 publications
0
31
0
2
Order By: Relevance
“…1a), for amicetin binding based on the results previously reported in the literature [12] and discussed above. The underlined nucleotides of the hexanucleotide linker (5Ј-CUUCGG-3Ј), occuring commonly in ribosomal RNAs, has been shown to form a stable tetraloop and confer high thermal stability [23].…”
Section: Design Synthesis and Stability Of Single-stranded 35mer Rnamentioning
confidence: 96%
See 4 more Smart Citations
“…1a), for amicetin binding based on the results previously reported in the literature [12] and discussed above. The underlined nucleotides of the hexanucleotide linker (5Ј-CUUCGG-3Ј), occuring commonly in ribosomal RNAs, has been shown to form a stable tetraloop and confer high thermal stability [23].…”
Section: Design Synthesis and Stability Of Single-stranded 35mer Rnamentioning
confidence: 96%
“…1a) [4,5]. However, based on more recent experiments, it has been revealed that antibiotic inhibition of peptide transfer can also take place by other mechanisms, attributing functional and structural roles for analogous conserved structural motifs lying adjacent to the catalytic transfer centre [1,12]. One such antibiotic, amicetin, belongs to a functionally related family of drugs which share a hexosecytosine moiety (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations